2018
DOI: 10.15406/jdmdc.2018.05.00130
|View full text |Cite
|
Sign up to set email alerts
|

Association of ABO blood groups with type-2 diabetes mellitus and its complications

Abstract: Background: As type 2 DM has posed challenging and formidable problem globally lots of scientific research work have been targeted and concepts are evolving every other day to unleash newer etiological factor in its causation and side by side risk factors so that proper aggressive strategy can be instituted to contain the disease at the very outset. Keeping these ideas in the back of our mind we embarked upon this small but compact path finding study. Methodology:The study conducted in the Dept. of Endocrinolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
3
11
1
Order By: Relevance
“…They observed that blood group "B +ve" was more frequent in diabetic patients (30.8%) compared to the control group (24.9%). Mandal B et al (11) have found that people with O +ve blood group have the least chance of developing T2DM. Similar observations were also seen when the distribution of ABO and Rh blood groups in males and females were separately analysed (refer Pie charts 1-12) in the present study, suggesting that blood group B +ve has the highest risk for T2DM among both genders.…”
Section: Resultsmentioning
confidence: 99%
“…They observed that blood group "B +ve" was more frequent in diabetic patients (30.8%) compared to the control group (24.9%). Mandal B et al (11) have found that people with O +ve blood group have the least chance of developing T2DM. Similar observations were also seen when the distribution of ABO and Rh blood groups in males and females were separately analysed (refer Pie charts 1-12) in the present study, suggesting that blood group B +ve has the highest risk for T2DM among both genders.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between blood group and diabetes was not statistically significant, according to Ebeye et al [24], but the percentage of blood group A and blood group O in the case group (diabetic patients) was the lowest and the highest among the blood groups, respectively. Mandal et al [22] concluded that no statistically significant relationship was observed between blood groups in the diabetic and non-diabetic population. However, relative risk was calculated among the blood groups AB (1.075), A (1.044) and B (1.033) compared to the blood group O.…”
Section: Discussion/conclusionmentioning
confidence: 98%
“…Then, the multivariate regression model is applied and the odds ratios based on the multivariate model results were calculated and reported. In the multivariate regression model, blood group O is considered as the reference group according to the same pervious study [22]. Software SPSS V.21 was used for statistical analysis and the significance level was set at 0.05.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…India is the country with the largest number of diabetic people with around 32 million in 2015 and is predicted to be increased to 80 million by the year 2030 (Oner et al, 2016). Type-II DM results in failure of multiple organ systems, thus leading to morbidity and mortality, imposing a major burden on the patient and the health care team (Mandal et al, 2018). Many studies were conducted to determine an imaginable suggestion among ABO and Rh blood groups and Type-II DM and reported that there is a strong relation between Type-II DM and ABO blood groups (Ganesan and Gani, 2014).…”
Section: Introductionmentioning
confidence: 99%